Surface modification of nanoparticle and natural fiber fillers - Mittal, Vikas (Polymer nano-, micro- & macrocomposites., 2015)
A review of the various methodologies for the surface treatment of different types of inorganic spherical and fibrous fillers, describing ball milling, cationic polymerization, vapor phase grafting, plasma treatment and UV irradiation in detail. In addition, the book connects the resulting composite properties to the modified filler surface properties, thus allowing for a purposeful, application-oriented composite design.